Paperwork and the Will of Capital: Taryn Simon - Simon, Taryn (Hatje Cantz Verlag; Gagosian Gallery, NY, 2016)
Exhibition catalog. Texts: Kate Fowle, Nicholas Kulish, Hanan alShaykh.
English
Keywords: N4390-5098 Visual Arts- Exhibitions